2021
DOI: 10.1192/j.eurpsy.2021.718
|View full text |Cite
|
Sign up to set email alerts
|

Professional burnout and increased workload during covid-19 in higher education teachers in monteria - colombia

Abstract: Introduction Faced with the global health emergency, a product of Covid-19, the educational system was forced to change its dynamics, assuming new challenges and adapting to virtual environments (Sierra, López, Azar & Trevethan, 2020). In this sense, the teaching task from home supposes an increase in the hours dedicated to their work, since they have seen the need to be trained in digital platforms to be able to respond to the changes derived from confinement; which can quietly generate professional wear … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…In a study conducted to analyze the levels of stress, anxiety, and depression of educators in the north of Spain at the beginning of the academic year during the COVID-19 pandemic, 49.3% of the educators surveyed showed anxious symptomatology, 50.4% showed stress symptomatology, and 32.2% of the educators showed a certain degree of depressive symptomatology (Santamaría et al, 2021). Another study conducted in Colombia by Gonzalez et al (2021) showed that 54% of the interviewees perceive a moderate stress level while 31% perceived high stress levels. For planners and practitioners, the shift to online learning led to an increased workload, uncertainty, technical challenges, and concerns for student well-being.…”
Section: Negative Health Impactmentioning
confidence: 98%
See 1 more Smart Citation
“…In a study conducted to analyze the levels of stress, anxiety, and depression of educators in the north of Spain at the beginning of the academic year during the COVID-19 pandemic, 49.3% of the educators surveyed showed anxious symptomatology, 50.4% showed stress symptomatology, and 32.2% of the educators showed a certain degree of depressive symptomatology (Santamaría et al, 2021). Another study conducted in Colombia by Gonzalez et al (2021) showed that 54% of the interviewees perceive a moderate stress level while 31% perceived high stress levels. For planners and practitioners, the shift to online learning led to an increased workload, uncertainty, technical challenges, and concerns for student well-being.…”
Section: Negative Health Impactmentioning
confidence: 98%
“…In addition to additional stress on students, research has shown that the switch to online learning during the COVID-19 pandemic has significantly impacted the mental health of higher education educators, particularly in the areas of workload and burnout (Gonzalez et al, 2021). In a cross-sectional study of 166 educators in Montería, Colombia, Gonzalez and colleagues found that educators experienced an increase in workload during the pandemic, which was associated with higher levels of emotional exhaustion, depersonalization, and reduced personal accomplishment.…”
Section: Mental Health Effectsmentioning
confidence: 99%
“…Specifically, in the US, Peacock (2022) found that more than half of the staff had greater stress and anxiety, and in other countries in Europe, HE staff suffered a great deal of stress due to the pandemic (Kundu et al, 2022). The UK case is also similar to Colombia (Gonzalez et al, 2021) and Finland (Laukkala et al, 2021), where evidence suggests that the increased workload resulted in elevated HE staff stress levels, as well as to South Africa, where cutting off social ties impacted HE staff's wellbeing and mental health (Olawale et al, 2021). On the other hand, our results disagree with Dinu et al (2021) conclusion that academic wellbeing levels were not significantly predicted by workload increases, as staff in our study reported the increased workload as a primary cause for stress and anxiety, significantly harming their wellbeing.…”
Section: Theme # 1: Covid-19 and Uk He Staff's Wellbeing And Mental H...mentioning
confidence: 99%
“…In the meantime, HE staff had to adjust to online teaching and increased workload, further impacting their wellbeing and mental health. Gonzalez et al (2021) analysed the relationship between professional burnout and increased workload on academics in Colombia during the pandemic and discovered a 50% increase in their workload. They concluded that the significant increase in the workload of academics correlates positively with levels of emotional exhaustion and depersonalisation.…”
Section: Literature Reviewinsights and Gapsmentioning
confidence: 99%
“…Hypothesis: According to previous research (Gonzalez et al, 2021;Santamaría et al, 2021;Arrona-Palacios et al, 2022) university teachers' stress, anxiety, and burnout increased during the COVID-19 pandemic and the intention to leave the teaching career has increased due the COVID-19 pandemic among school teachers (Collie, 2022;Zamarro et al, 2022). Furthermore, previous research shows that university teachers' experiences of stress and burnout have been shown to predict turnover intention among HE professionals (Winfield and Paris, 2021).…”
Section: Introductionmentioning
confidence: 95%